Politicisation of Agrarian Legal Conflict as Political Capital: A Fiqh Siyasah Perspective - Agus Machfud Fauzi; Novi Fitia Maliha; Iffatin Nur; Ahmad Ridwan; Eufrasia Kartika Hanindraputri; Mohammad Reevany Bustami (De Jure: Jurnal Hukum dan Syari'ah, 2026)
Urban agrarian legal conflicts in Indonesia started to arise following state land governance policies and the acceleration of land asset certification, raising questions about land rights and legal protection for long-term residents. During the 2024 Surabaya mayoral election, tensions intensified as PT Kereta Api Indonesia (PT KAI) accelerated land-asset certification, affecting residents in several urban neighbourhoods. The dispute over the legal certainty of land rights entered the electoral arena and was politicised by political elites as a strategy to mobilise support and secure electoral victory. This article examines how agrarian legal conflict is politicised as political capital and how affected residents interpret and respond to limited political choices when their right to the city is under threat. A qualitative approach was employed through field observation, document analysis, and in-depth interviews conducted in three affected sub-districts in Surabaya: Petemon, Gundih, and Pacar Keling. The analysis integrates the theory of political representation developed by Hanna Pitkin with the perspective of fiqh siyasah concerning ‘adl (justice), maslahah (public welfare), and political legitimacy as articulated by Abu al-Hasan al-Mawardi. The findings reveal three patterns of political responses among affected residents: political apathy due to weakened channels of representation; clientelistic co-optation through neighbourhood governance networks, such as RT/RW, accompanied by promises of compensation; and electoral resistance expressed through support for the empty-box option. Politicising agrarian legal conflict proved effective as political capital, leading to a procedural electoral victory. However, from a fiqh siyasah perspective, political legitimacy cannot be determined solely by electoral success but must also reflect justice and the protection of public welfare. This study contributes theoretically by employing fiqh siyasah as an analytical framework to evaluate the gap between procedural electoral victory and normative legitimacy in urban agrarian conflicts. Keywords: agrarian legal conflict; political capital; electoral politics; fiqh siyasah; political representation